Sirtuin 1 and Autophagy Attenuate Cisplatin-Induced Hair Cell Death in the Mouse Cochlea and Zebrafish Lateral Line - Pang, Jiaqi; Xiong, Hao; Zhan, Ting; Cheng, Gui; Jia, Haiying; Ye, Yongyi; Su, Zhongwu; Chen, Hongyu; Lin, Hanqing; Lai, Lan; Ou, Yongkang; Xu, Yaodong; et al. (Frontiers in Cellular Neuroscience, 2019)
Cisplatin-induced ototoxicity is one of the major adverse effects in cisplatin chemotherapy, and hearing protective approaches are unavailable in clinical trial. Recent work unveiled a critical role of autophagy in cell survival in various types of hearing loss. Since the excessive activation of autophagy can contribute to apoptotic cell death, whether the activation of autophagy increases or decreases the rate of cell death in cisplatin ototoxicity is still being debated. In this study, we showed that cisplatin induced activation of autophagy in the auditory cell HEI-OC1 at the early stage. We then used rapamycin, an autophagy activator, to increase the autophagy activity and found that the cell death significantly decreased after cisplatin injury. In contrast, treatment with the autophagy inhibitor 3-methyladenine (3-MA) resulted in reduced autophagy activity and significantly increased cell death. In accordance with the vitro results, rapamycin alleviated cisplatin induced death of the lateral line hair cells in zebrafish and cochlear hair cells in mice. Notably, we first found that cisplatin-induced increase of Sirtuin 1 (SIRT1) in the HEI-OC1 cells modulated the autophagy function. The specific SIRT1 activator could successfully prevent the increase of hair cell death both in HEI-OC1 cells and in the cochlea of mice after cisplatin exposure. These findings demonstrate that there is a protective way for the sensory hair cells to rescue themselves by raising SIRT1 expression and autophagy activity at the early stage of cisplatin injury. SIRT1 and autophagy activation can be suggested as potential therapeutic strategies for overcoming the cisplatin-induced ototoxicity.